INTERNATIONAL LAW REVIEW ON THE EXPLOITATION AND NEGLECT OF INDONESIAN WORKERS IN MALAYSIA - Gunawan, Yordan; Farman, Logi; Jayapraja, Labib Dianatadilaga; Taufik, Muhammad Sulthan Faqih; Irrynta , Dwilani (Wacana Hukum, 2022)
With the increasing number of Indonesian workers in Malaysia, theproblems related to the supervision and protection of workers inare also more and greater in accordance to the international legalnorm. Malaysia has identified to commit human rights violations ingeneral and labor rights, in particular exploitation and neglect ofworkers, which contradicts the Memorandum of Understanding(MoU) between Indonesia and Malaysia along with the InternationalLabor Organization (ILO) Conventions. In the case of a worker withthe initial YT(60), his employer was identified as not providingwages for 7.5 years and it was faund in 2022. The research usednormative legal methods. The source and data used in this study aresecondary sources in the form of legal materials. The result showedthat the applicable MoU between the two countries is adequate, yetMalaysia was identified to violate some provisions in the MoU itself.Therefore, there is an urgency for the two countries to reinforcelaws regarding such issues, including a more detailed agreementregarding the placement and all rights of migrant workers regulatedby the national law of the receiving country, namely Malaysia